2015
DOI: 10.1002/pmic.201400400
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SUMO-2/3-modified proteins associated with mitotic chromosomes

Abstract: Sumoylation is essential for progression through mitosis, but the specific protein targets and functions remain poorly understood. In this study, we used chromosome spreads to more precisely define the localization of SUMO-2/3 to the inner-centromere and protein scaffold of mitotic chromosomes. We also developed methods to immunopurify proteins modified by endogenous, untagged SUMO-2/3 from mitotic chromosomes. Using these methods we identified 149 chromosome-associated SUMO-2/3 substrates by nLC-ESI-MS/MS. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 48 publications
(73 reference statements)
1
36
0
Order By: Relevance
“…This localization pattern is reminiscent of that of SUMO-1 and SUMO-2/3 during mitosis (Zhang et al., 2008), and the only SUMO isoform in nematodes displays a combination of these localization patterns during the first embryonic mitotic division (Pelisch et al., 2014). Many SUMO substrates are involved in chromatin structure and function (Cubeñas-Potts and Matunis, 2013), and KIF4A, the human ortholog of KLP-19, has been identified as a SUMO substrate in mitotic chromatin (Cubeñas-Potts et al., 2015). These observations support the notion that while precise mechanisms that guarantee proper chromosome orientation, congression, and segregation might differ between meiosis and mitosis and also among species, SUMO is likely a key contributor to a timely and accurate regulation of protein interactions within narrow spatial and temporal windows.…”
Section: Discussionmentioning
confidence: 99%
“…This localization pattern is reminiscent of that of SUMO-1 and SUMO-2/3 during mitosis (Zhang et al., 2008), and the only SUMO isoform in nematodes displays a combination of these localization patterns during the first embryonic mitotic division (Pelisch et al., 2014). Many SUMO substrates are involved in chromatin structure and function (Cubeñas-Potts and Matunis, 2013), and KIF4A, the human ortholog of KLP-19, has been identified as a SUMO substrate in mitotic chromatin (Cubeñas-Potts et al., 2015). These observations support the notion that while precise mechanisms that guarantee proper chromosome orientation, congression, and segregation might differ between meiosis and mitosis and also among species, SUMO is likely a key contributor to a timely and accurate regulation of protein interactions within narrow spatial and temporal windows.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several efforts have been made to study sumoylation on a global and site-specific manner by high resolution mass spectrometry (14,15,(51)(52)(53)(54). Reanalyzing all these available data sets (13) revealed that at physiological conditions, at least half of the SUMO substrates are modified at the minimal KxE motif, although upon stress, more lysines at non-SCM sites are modified.…”
Section: The Sumo Consensus Motifmentioning
confidence: 99%
“…Indeed, more than 1000 sumoylated proteins have been identified, with the numbers continuously increasing (13). Sumoylation is highly dynamic and the global SUMO proteome is constantly changing, for example, during cell cycle progression and cell differentiation, and it is drastically induced upon stress (14)(15)(16)(17). Such stress stimuli include DNA damage, heat shock, proteasomal inhibition, viral infection or ischemic challenge.…”
Section: Introductionmentioning
confidence: 99%
“…These proteomic approaches have also greatly helped in identifying other SUMO target proteins essential for cell cycle progression and have uncovered global SUMO dynamics throughout the cell cycle [23,55]. It would be interesting to identify groups of specific substrates regulated by the different dynamic SUMO machinery components.…”
Section: Sumoylation and Cyclin-dependent Kinases In Concertmentioning
confidence: 99%
“…Additional CDKs and cyclins have been identified as SUMO targets in recent proteomic screens and targeted approaches, including CDK1, CDK9, CDK11 and Cyclin-E, further highlighting crosstalk between SUMOylation and phosphorylation during cell cycle regulation [23,48,54] (Figure 2). These proteomic approaches have also greatly helped in identifying other SUMO target proteins essential for cell cycle progression and have uncovered global SUMO dynamics throughout the cell cycle [23,55]. It would be interesting to identify groups of specific substrates regulated by the different dynamic SUMO machinery components.…”
mentioning
confidence: 99%